No Compensation for Animals Felony" Rule: Applied jurisprudence study" - Bhais, Marwan Ibraheem (Journal of Islamic Sciences, 2021)
This research was built from an introduction and two chapters, and it was relied on the descriptive approach with the use of the deductive and inductive approaches, and it mainly aimed at explaining the rule of no compensation in the crime of animals and highlighting its ancient and contemporary applications: where the study showed the importance of this jurisprudential rule and its role in solving many contemporary issues related to Felonies committed against oneself or others, or property.The study also showed the applicability of many contemporary images of means of transportation and equipment, used in workplaces by contractors, war and military parts, factories and machinery, on the basis of no compensation in animal felony.The study clarified the discipline of not trespassing or negligence, and accordingly, the verdict of the car, plane, train and heavy equipment felony is attached without transgression or negligence in the animal felony ruling.The researcher suggests including the rule that there is no compensation in animal felony in the traffic rules and traffic laws to be the final ruling in the case of litigation for the law.
Keywords: rule; felony; beasts; non- guarantee of loss; contemporary